Demokrasi dan ketimpangan pendapatan di Indonesia - Nurul Bariyah (Jurnal Ilmiah Mimbar Demokrasi, 2022)
Abstract: The concept of democracy and income inequality has become a topic of study by many economists around the world, both in isolation and in conjunction with other concepts in the field of economics. The fifth principle of Pancasila states "Social justice for all Indonesian people". When viewed from the aspect of income, justice means equality. This study aims to analyze the effect of the Indonesian Democracy Index on Income Inequality in 34 provinces in Indonesia from 2009 to 2019. The Democracy Index is examined through its three aspects (Civil Liberties, Political Rights, and Democratic Institutions), and Income Inequality is measured by the Indonesian Gini Index. The effect of IDI on IGI was analyzed by using the Fixed Effect Model using data quoted from official sources, which is the Central Bureau of Statistics. The results of the Multiple Linear Regression estimation show that 15 provinces get a positive value where the rise in IDI is followed by a rise in IGI and 19 provinces show a negative value which means that the rise in IDI is not followed by a rise in IGI (Income Inequality). The disaggregation of the democracy index in this study is expected to provide a clear picture of the relationship between civil liberties, political rights and democratic institutions with income inequality, so that appropriate policies can be formulated to address income inequality in Indonesia. Abstrak: Konsep demokrasi dan ketimpangan pendapatan telah menjadi topik kajian dari banyak ahli ekonomi di seluruh dunia, baik secara sendiri maupun dalam hubungannya dengan konsep-konsep lain dalam bidang ekonomi. Jika dilihat dari Sila Kelima Pancasila yang berbunyi “Keadilan sosial bagi seluruh rakyat Indonesia”, maka keadilan adalah pemerataan atau equality dalam memperoleh pendapatan yang adil, sesuai dengan kegiatan yang dilakukannya. Penelitian ini bertujuan menganalisis pengaruh Indeks Demokrasi Indonesia terhadap Ketimpangan Pendapatan pada 34 provinsi di Indonesia dari tahun 2009 sampai 2019. Indeks Demokrasi diteliti melalui ketiga aspeknya (Kebebasan Sipil, Hak-hak Politik, dan Lembaga Demokrasi), dan Ketimpangan Pendapatan diukur dengan Indeks Gini Indonesia. Pengaruh IDI terhadap IGI dianalisis dengan menggunakan Fixed Effect Model dengan menggunakan data yang dikutip dari sumber resmi Biro Pusat Statistik. Hasil estimasi Regresi Linier Berganda menunjukkan bahwa 15 provinsi memperoleh nilai positif di mana kenaikan IDI diikuti kenaikan IGI dan 19 provinsi menunjukkan nilai negatif yang berarti kenaikan IDI tidak diikuti kenaikan IGI (Ketimpangan Pendapatan). Disagregasi indeks demokrasi dalam penelitian ini diharapkan dapat memberikan gambaran yang jelas mengenai keterkaitan kebebasan sipil, hak politik dan kelembagaan demokrasi dengan ketimpangan pendiapatan, sehingga dapat diformulasikan kebijakan yang tepat untuk mengatasi ketimpangan pendapatan di Indonesia.